Occupancy detection and estimation using smartphone - Kruthika Priyadharshini A. (2017)
Currently, the focus on energy consumption reduction and efforts to reduce climate change has been spoken about widely. The recent Paris Agreement is a testimony to that. The need to reduce the consumption of energy is all places has become paramount. The technology that has been made use of to combat these problems has mostly been revolved around sensors such as motion and carbon dioxide. Wi-Fi which is a technology with devices set on the IEEE 802.11 standards for WLAN can be a viable method to achieve energy efficiency. Wi-Fi is a standard feature of smartphones across brands and is continuously improved fuelled by the demand in the smartphone industry. Hence the already provided structure of WLAN connections can be leveraged on for the purpose of occupancy detection. Moreover, the rise is the ubiquity of smartphones has allowed for the exploitation of the wireless connectivity capability that they are already equipped with. This project analyses the various methods that can be undertaken with regards to smartphone and Wi-Fi to detect occupancy is an indoor environment and concludes with lean algorithms and a test the accuracy so that they can be implemented in smartphone environments to retrieve location information of smartphones which can be used for occupancy estimation.